2014
DOI: 10.1007/s00253-014-5527-8
|View full text |Cite
|
Sign up to set email alerts
|

BioBrickTM compatible vector system for protein expression in Rhodobacter sphaeroides

Abstract: We report here the creation of a modular, plasmid-based protein expression system utilizing elements of the native Rhodobacter puf promoter in a BioBrick(TM)-based vector system with DsRed encoding a red fluorescent reporter protein. A suite of truncations of the puf promoter were made to assess the influence of different portions of this promoter on expression of heterologous proteins. The 3' end of puf was found to be particularly important for increasing expression, with transformants accumulating significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…4B). To ensure that this result was due to deletion of rsp_6110, rather than a polar effect on acsF, rsp_6110 was expressed in trans in ΔbchEΔccoPΔ6110 from pBBRBB-Ppuf 843-1200 (27). Pigments from this strain were analyzed as above, and Mg-BChl a and Zn-BChl a were detected in this extract (Fig.…”
Section: Bioinformatic Analysis Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…4B). To ensure that this result was due to deletion of rsp_6110, rather than a polar effect on acsF, rsp_6110 was expressed in trans in ΔbchEΔccoPΔ6110 from pBBRBB-Ppuf 843-1200 (27). Pigments from this strain were analyzed as above, and Mg-BChl a and Zn-BChl a were detected in this extract (Fig.…”
Section: Bioinformatic Analysis Of Amentioning
confidence: 99%
“…The pBB[gene] plasmid was used to express foreign genes in Rba. sphaeroides and was constructed by cloning the relevant ORF between BglII/NotI sites in pBBRBB-Ppuf 843-1200 (27). Rvi.…”
Section: Construction Of Mutantsmentioning
confidence: 99%
“…Δ pufQ mutant cells are orange in colour, as are many others harbouring mutations that abolish BChl biosynthesis. The pufQ gene was reintroduced to the Δ pufQ strain using the pBBRBB‐ Ppuf 843–1200 plasmid (Tikh et al ., ). pBBRBB‐ pufQ transconjugants displayed a WT‐like phenotype, with elevated levels of LH2 complexes (800 and 850 nm absorption), indicating that BChl biosynthesis has been restored and implying that the Δ pufQ phenotype does not arise from polar effects (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, the absence of carotenoids in the Δ crtB strain used for this work could have created a need for photoprotective pigments, and it has been suggested that fluorescent proteins can play a photoprotective role2627. To confirm that the superior growth rate of the Δ crtB RC/YFP–LH1 strain (versus the Δ crtB negative control) was due to YFP energy transfer and not photoprotection (which could favour an increased growth rate), the expression plasmid pBBRBB–YFP, based on pBBRBB- Ppuf 843–1200 28, was used to make cytoplasmic YFP in Rba. sphaeroides Δ crtB , which is free of any attachment to membrane proteins.…”
Section: Resultsmentioning
confidence: 99%